2011
DOI: 10.3122/jabfm.2011.01.100219
|View full text |Cite
|
Sign up to set email alerts
|

Neurofibromatosis Type 1: Persisting Misidentification of the "Elephant Man" Disease

Abstract: Background: During informal interviews in the course of an ethnographic study on intergenerational dialogue between individuals with neurofibromatosis and their parents, many members of Canadian neurofibromatosis associations have stated that they continue to be told the condition that afflicts them or their children is "elephant man's disease." Today, even though well-established clinical criteria make it possible to diagnose and differentiate the 2 diseases, the confusion between neurofibromatosis type 1 (NF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Doctor-patient communication influences many entities and patient experiences, including back pain, exercise counseling, preferences for depression treatment, prehypertension, and individual entities such as neurofibromatosis 3 and Huntington disease. 4 Two articles in this issue use standard techniques for analysis of audio-recorded visits to study specific provider-patient communications.…”
Section: Doctor Communication Influences Many Entities and Patient Exmentioning
confidence: 99%
“…Doctor-patient communication influences many entities and patient experiences, including back pain, exercise counseling, preferences for depression treatment, prehypertension, and individual entities such as neurofibromatosis 3 and Huntington disease. 4 Two articles in this issue use standard techniques for analysis of audio-recorded visits to study specific provider-patient communications.…”
Section: Doctor Communication Influences Many Entities and Patient Exmentioning
confidence: 99%
“…Neurofibromatosis 1 offers one example of this complexity. Half of the time, neurofibromatosis 1 results from a de-novo mutation, while half of the time it is hereditary in an autosomal dominant mode (Legendre et al, 2011). It is also one of the world's most widespread orphan genetic disorders with a prevalence of one in every 3000, almost identical to the far better known cystic fibrosis, with a prevalence of one in every 2500 (Legendre et al, 2011).…”
Section: The Recognition Of Beneficiaries' Continued Free Agencymentioning
confidence: 99%
“…Half of the time, neurofibromatosis 1 results from a de-novo mutation, while half of the time it is hereditary in an autosomal dominant mode (Legendre et al, 2011). It is also one of the world's most widespread orphan genetic disorders with a prevalence of one in every 3000, almost identical to the far better known cystic fibrosis, with a prevalence of one in every 2500 (Legendre et al, 2011). Nevertheless, in 2012, it was reported that five children fathered by a sperm donor (who had exported his spermatozoa to 10 countries and fathered 43 known children) had been diagnosed with neurofibromatosis 1 (Human Fertilisation and Embryology Authority, 2012b).…”
Section: The Recognition Of Beneficiaries' Continued Free Agencymentioning
confidence: 99%
“…But, a discriminating diagnosis is required according to many other syndromes distinguishing themselves by asymmetric neoplasm [1][2][3]. In those syndromes, especially Proteus has an importance [4][5][6][7][8][9]. The most common clinical features in NF-1 are cafe-au-lait stains on the skin, cutaneous neurofibromas, freckling in skinfolds and Lisch nodules (iris hamartoma).…”
Section: Introductionmentioning
confidence: 99%